2005
DOI: 10.1016/j.jneuroim.2005.06.002
|View full text |Cite
|
Sign up to set email alerts
|

Lack of association with the CD28/CTLA4/ICOS gene region among Norwegian multiple sclerosis patients

Abstract: Chromosome region 2q33 encodes several regulators of the immune system, among these the CD28, CTLA4, and ICOS molecules. Involvement of these genes in multiple sclerosis (MS) is not yet clear. We investigated six microsatellites and three SNPs in a relatively large and clinically well characterised Norwegian MS cohort. No associations were observed for any of the markers analysed in 575 MS patients and 551 controls. Associations were neither found when stratifying the material for the HLA-DRB1*1501, DQB1*0602 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 128 publications
(190 reference statements)
2
24
1
Order By: Relevance
“…The observed separation between homoduplexes would allow for direct genotyping as compared to an internal standard as previously reported [13,15,17,30,31]. As previously published, when genotyping the same sample set with CTCE, TaqMan, and RFLP, the first two methods gave the same genotypes whereas RFLP had about 3% differences in the genotypes called.…”
Section: Resultssupporting
confidence: 71%
See 1 more Smart Citation
“…The observed separation between homoduplexes would allow for direct genotyping as compared to an internal standard as previously reported [13,15,17,30,31]. As previously published, when genotyping the same sample set with CTCE, TaqMan, and RFLP, the first two methods gave the same genotypes whereas RFLP had about 3% differences in the genotypes called.…”
Section: Resultssupporting
confidence: 71%
“…As previously published, when genotyping the same sample set with CTCE, TaqMan, and RFLP, the first two methods gave the same genotypes whereas RFLP had about 3% differences in the genotypes called. Evaluation of the data revealed that the differences in data were due to insufficient enzymatic cleavage of the polymorphic site [30]. However, care must be applied when using CTCE as a genotyping method because the CTCE is in general as scanning method; thus, new unknown variants within the target sequence could potentially lead to an error in the genotyping [25].…”
Section: Resultsmentioning
confidence: 99%
“…The G 49 allele of CTLA-4 was associated with MS susceptibility in two Scandinavian casecontrol studies (Harbo et al, 1999;Ligers et al, 1999) as well as in Olmsted County (Kantarci et al, 2003), and may influence disease severity in Japanese MS (Fukazawa et al, 1999b). However, multiple other case-control studies found no association with MS susceptibility (Masterman et al, 2000;Rasmussen et al, 2001;Bocko et al, 2003;van Veen et al, 2003a;Bonetti et al, 2004;Teutsch et al, 2004;Fukazawa et al, 2005;Lorentzen et al, 2005;Roxburgh et al, 2006). A family-based study in Canadian MS also found no association (Dyment et al, 2004); however, familybased studies with replication in French and southern European MS found an association, especially in families carrying the HLA-DRB1*15 haplotype (Alizadeh et al, 2003).…”
Section: Cytotoxic T-lymphocyte-associated Protein 4 (Ctla-4 or Cd152)mentioning
confidence: 97%
“…The clinical importance of this finding is illustrated in humans by reports of patients with a homozygous deletion of ICOS associated with common variable immunodeficiency characterized by defects in Ab production and susceptibility to bacterial infections (24). Moreover, T cells from these patients display no defects in cytokine production or proliferation when stimulated ex vivo and, similar to the studies in murine models, the role of ICOS during the generation of T cell responses in humans has been harder to define (25)(26)(27)(28).…”
Section: S Uccessful Activation Of T Cells Requires a Primary Signalmentioning
confidence: 99%